The Representation of the Bible in Painting - Paula-Andreea Onofrei (Anastasis: Research in Medieval Culture and Art)
book review: Gérard Denizeau, Biblia în pictura universală [The Bible in Universal Painting], Larousse, Rao Publishing House, Bucharest, 2016, 226 pages